From Cadet to Captain: Christian Faith, Happiness, and Moral Resilience Across the Maritime Career Lifespan: Dari Taruna hingga Kapten: Iman Kristen, Kebahagiaan, dan Ketahanan Moral Sepanjang Perjalanan Karier Maritim - Marihot Simanjuntak; Brenhard Mangatur Tampubolon (SERVIRE: Jurnal Penelitian dan Pengabdian, 2026)
The maritime profession demands one of the longest sustained engagements with high-demand work that any career requires, yet the inner architecture by which maritime professionals sustain themselves across this lifespan has remained almost entirely unstudied. This qualitative study, employing a phenomenologically informed thematic approach within the transcendental phenomenological tradition associated with Moustakas, examined how Christian faith, happiness, and moral resilience are described across the maritime career lifespan, drawing on the testimony of thirty cadets at Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta together with five lecturers, three veteran seafarers, and two veteran port masters. Data were collected through in-depth semi-structured interviews and life-history conversations and analysed through a procedure combining epoché, horizonalisation, thematic clustering, and the construction of textural-structural descriptions, supplemented by cross-group comparison and narrative synthesis. The findings suggest that faith is generally described as a stable orientation that participants associate with deepening through difficult experience, although a minority of participants also described periods of doubt, spiritual struggle, or distancing that complicate any uniformly positive account. Happiness is described by many participants as an inner orientation distinct from momentary affect, and veterans' retrospective accounts suggest a pattern resembling a U-shaped trajectory across the career, a pattern we present as a hypothesis grounded in retrospective testimony from five veterans rather than as longitudinally confirmed evidence. Moral resilience is described as developing through repeated encounters with ethical challenge.